Multivariable Analysis of Clinical Influence Factors on Liver Enhancement of Gd-EOB-DTPA-Enhanced 3T MRI - Verloh, N.; Haimerl, M.; Zeman, F.; Teufel, A.; Lang, S.; Stroszczynski, C.; Fellner, C.; Wiggermann, P. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2015)
Purpose: The purpose of this study was to identify clinical factors influencing Gd-EOB-DTPA liver uptake in patients with healthy liver parenchyma.Materials and Methods: A total of 124 patients underwent contrast-enhanced MRI with a hepatocyte-specific contrast agent at 3 T. T1-weighted volume interpolated breath-hold examination (VIBE) sequences with fat suppression were acquired before and 20 minutes after contrast injection. The relative enhancement (RE) between plain and contrast-enhanced signal intensity was calculated. Simple and multiple linear regression analyses were performed to evaluate clinical factors influencing the relative enhancement. Patients were subdivided into three groups according to their relative liver enhancement (HRE, RE ≥ 100 %; MRE, 100 % > RE > 50 %; NRE, RE ≤ 50 %) and were analyzed according to the relevant risk factors.Results: Simple regression analyses revealed patient age, transaminases (AST, ALT, GGT), liver, spleen and delta-liver volume (the difference between the volumetrically measured liver volume and the estimated liver volume based on body weight) as significant factors influencing relative enhancement. In the multiple analysis the transaminase AST, spleen and delta liver volume remained significant factors influencing relative enhancement. Delta liver volume showed a significant difference between all analyzed groups.Conclusion: Liver enhancement in the hepatobiliary phase depends on a variety of factors. Body weight-adapted administration of Gd-EOB-DTPA may lead to inadequate liver enhancement after 20 minutes especially when the actual liver volume differs from the expected volume.Key Points:• Differences between actual and expected liver volume can cause inadequate liver enhancement after 20 min.• A liver volume-adapted dose of Gd-EOB-DTPA may help to improve liver enhancement.Citation Format:• Verloh N, Haimerl M, Zeman F et al. Multivariable Analysis of Clinical Influence Factors on Liver Enhancement of Gd-EOB-DTPA-Enhanced 3T MRI. Fortschr Röntgenstr 2015; 187: 29 – 35
Keywords: abdomen; MR imaging; contrast agents